On-Farm Assessment of System Productivity of Wheat-Jute-T. Aman Rice Cropping Pattern in Sylhet Region - Nazrul, MI (Bangladesh Agronomy Journal, 2017)
The study was conducted to determine the yield and economic performance of two cropping patterns viz. IP: improved pattern (Wheat - Jute - T. aman) + improved management practice and FP: farmers pattern (Fallow - T. aus - T. aman) + management practice. The experiment was laid out in a randomized complete block design with six dispersed replications at farmers field in Sylhet region during two consecutive years of 2013-14 and 2014-15. Two years means data showed that the pattern with improved management practices provided 31% higher yield of T. aman rice and also contributed more rice equivalent yield compared to farmers practice. Sustainable yield index, production efficiency, and land use efficiency were the maximum with Wheat-Jute- T. aman cropping system. Similarly, highest mean gross margin and benefit cost ratio were attained in improved pattern. It was concluded that farmers of Sylhet region might follow Wheat (var. BARI Gom-26) - Jute (var. CVL-1) - T. aman (var. Binadhan-7) cropping system in medium high land for higher productivity and profitability. Bangladesh Agron. J. 2016 19(2): 87-94